2009
DOI: 10.1002/pro.45
|View full text |Cite
|
Sign up to set email alerts
|

Methionine oxidation in human IgG2 Fc decreases binding affinities to protein A and FcRn

Abstract: Susceptibility of methionine residues to oxidation is a significant issue of protein therapeutics. Methionine oxidation may limit the product's clinical efficacy or stability. We have studied kinetics of methionine oxidation in the Fc portion of the human IgG2 and its impact on the interaction with FcRn and Protein A. Our results confirm previously published observations for IgG1 that two analogous solvent-exposed methionine residues in IgG2, Met 252 and Met 428, oxidize more readily than the other methionine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
166
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(170 citation statements)
references
References 54 publications
(38 reference statements)
4
166
0
Order By: Relevance
“…6, 7), the affinity to FcRn should be evaluated as an important quality attribute related to the pharmacokinetic profile, even if the protein has a native Fc domain of IgG1, especially in cases of Fcfusion proteins. Meanwhile, because it was demonstrated that oxidation of two labile methionines, Met 252 and Met 428 , in human IgG1 attenuates binding of the Ab to FcRn (36), alteration of the affinity to FcRn during the production process or storage will reflect structural changes of the protein, including Met oxidation, that will lead to shortening the serum half-life. In addition to IgG, albumin is also known to bind to FcRn in a pH-dependent manner and is protected from degradation (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…6, 7), the affinity to FcRn should be evaluated as an important quality attribute related to the pharmacokinetic profile, even if the protein has a native Fc domain of IgG1, especially in cases of Fcfusion proteins. Meanwhile, because it was demonstrated that oxidation of two labile methionines, Met 252 and Met 428 , in human IgG1 attenuates binding of the Ab to FcRn (36), alteration of the affinity to FcRn during the production process or storage will reflect structural changes of the protein, including Met oxidation, that will lead to shortening the serum half-life. In addition to IgG, albumin is also known to bind to FcRn in a pH-dependent manner and is protected from degradation (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Amino acid residues near the Fc hinge region mutated to increase binding to FcRn are grouped in colors according to the various combination listed in Table 1. decreased binding to FcRn and subsequent loss of protection from catabolism. 60,61 To improve the circulating half-life of Fc-fusion protein, Fc-fusion "monomers" were created where single rather than dimeric therapeutic protein was fused to the dimeric Fc domain. 62 Fc-fusion monomer of erythropoietin, interferon (IFN)α, IFNβ and Factor IX have all been shown to have longer circulating half-lives in mouse or cynomolgus monkey than its dimeric counterpart and administration by pulmonary or oral route also resulted in enhanced bioavailability of the agents.…”
Section: Qlmentioning
confidence: 99%
“…Interestingly, posttranslational modifications such as oxidation of conserved methionines in the C H 2 and C H 3 domains of IgG 1 and IgG 2 have been shown to affect FcRn affinity negatively. Antibody oxidation that can occur during production or storage significantly reduces FcRn binding in vitro (20,21), which also translates to a reduced in vivo half-life in human FcRn transgenic mice models (22). The molecular origins of the effect of post-translational modifications on the IgG-FcRn interaction are, however, unclear.…”
mentioning
confidence: 99%